H.O.P.E. - He, Samuel. (2009)
This documentary short titled H.O.P.E. is produced by a group of graduating students from the Wee Kim Wee School of Communication and Information (WKWSCI) at the Nanyang Technological University (NTU), Singapore. H.O.P.E. tells the stories of a group of men in Manila, Philippines, who are donating their kidneys in return for financial compensation. This process is happening under a government regulated system that serves to tackle the problem of an unregulated organ black market. This report chronicles the filmmakers’ progress at every stage of production, from research to pre-production, production and finally, post production. Additionally, the report details the various challenges and ethical dilemmas faced by the film-makers and the decision-making process that followed.